Advances in Developing CAR T-Cell Therapy for HIV Cure - Qi, Jinxin; Ding, Chengchao; Jiang, Xian; Gao, Yong (Frontiers in Immunology, 2020)
Acquired immune deficiency syndrome (AIDS) caused by HIV infection is an epidemic disease killing millions of people in the last several decades. Although combination antiretroviral therapy (cART) has enabled tremendous progress in suppressing HIV replication, it fails to eliminate HIV latently infected cells, and infected individuals remain HIV positive for life. Lifelong antiretroviral therapy is required to maintain control of virus replication, which may result in significant problems, including long-term toxicity, high cost and stigma. Therefore, novel therapeutic strategies are urgently needed to eliminate the viral reservoir in the host for HIV cure. In this review, we compared several potential strategies regarding HIV cure and focused on how we might utilize chimeric antigen receptor modified T cell (CAR T) as a therapy to cure HIV infection.